Characterization of the functional activity of botulinum neurotoxin subtype B6. (16th November 2017) - Kohda, Tomoko; Nakamura, Keiji; Hosomi, Koji; Torii, Yasushi; Kozaki, Shunji; Mukamoto, Masafumi
ABSTRACT: Clostridium botulinum produces the highly potent neurotoxin, botulinum neurotoxin (BoNT), which is classified into seven serotypes (A–G); the subtype classification is confirmed by the diversity of amino acid sequences among the serotypes. BoNT from the Osaka05 strain is associated with type B infant botulism and has been classified as BoNT/B subtype B6 (BoNT/B6) by phylogenetic analysis and the antigenicity of its C‐terminal heavy chain (HC ) domain. However, the molecular bases for its properties, including its potency, are poorly understood. In this study, BoNT/B6 holotoxin was purified and the biological activity and receptor binding activity of BoNT/B6 compared with those of the previously‐characterized BoNT/B1 and BoNT/B2 subtypes. The derivative BoNT/B6 was found to be already nicked and in an activated form, indicating that endogenous protease production may be higher in this strain than in the other two strains. BoNT/B1 exhibited the greatest lethal activity in mice, followed by BoNT/B6, which is consistent with the sensitivity of PC12 cells. No significant differences were seen in the enzymatic activities of the BoNT/Bs against their substrate. HC /B1 and HC /B6 exhibited similar binding affinities to synaptotagmin II (SytII), which is a specific protein receptor for BoNT/B. Binding to the SytII/ganglioside complex is functionally related to the toxic action; however, the receptor recognition sites are conserved. These results suggest that the distinct characteristics and differences in biological sensitivity of BoNT/B6 may be attributable to the function of its Hc .domain.